2013
DOI: 10.1111/cei.12138
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Toll-like receptor 2 responses in the pathogenesis of pulmonary sarcoidosis

Abstract: SummaryIn this study, we hypothesized that the granulomatous disorder sarcoidosis is not caused by a single pathogen, but rather results from abnormal responses of Toll-like receptors (TLRs) to conserved bacterial elements. Unsorted bronchoalveolar lavage (BAL) cells from patients with suspected pulmonary sarcoidosis and healthy non-smoking control subjects were stimulated with representative ligands of TLR-2 (in both TLR-2/1 and TLR-2/6 heterodimers) and TLR-4. Responses were determined by assessing resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Because of conflicting reports on the role of various TLR gene polymorphisms in human populations regarding susceptibility to sarcoidosis (21,(33)(34)(35)(36), we attempted to investigate the role of multiple TLRs simultaneously by using MyD88, a downstream adapter molecule in proinflammatory TLR/IL1R superfamily signaling (23). At least one targeted gene study has linked polymorphisms in MyD88 with susceptibility to sarcoidosis in a human population (37).…”
Section: Discussionmentioning
confidence: 99%
“…Because of conflicting reports on the role of various TLR gene polymorphisms in human populations regarding susceptibility to sarcoidosis (21,(33)(34)(35)(36), we attempted to investigate the role of multiple TLRs simultaneously by using MyD88, a downstream adapter molecule in proinflammatory TLR/IL1R superfamily signaling (23). At least one targeted gene study has linked polymorphisms in MyD88 with susceptibility to sarcoidosis in a human population (37).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene-linkage studies have identified polymorphisms in the genes encoding TNF and its receptor to be associated with differential susceptibility to acute and chronic clinical courses in sarcoidosis [34][35][36]. Notably, studies have demonstrated enhanced responses to TLR2 stimulation, including enhanced induction of TNF, in cells from the blood and lung of sarcoidosis patients [37][38][39] (Table 1). TLR2 interacts with innate ligands as a heterodimer with other TLR subunits; an analysis of the TLR10-TLR1-TLR6 gene cluster on chromosome 4 suggests that absence of the common haplotype is associated with increased risk for developing chronic active disease in patients who initially presented with Löfgren syndrome [40].…”
Section: Genetic and Immunologic Interactions In Sarcoidosis Etiologymentioning
confidence: 99%
“…TLR2 interacts with innate ligands as a heterodimer with other TLR subunits; an analysis of the TLR10-TLR1-TLR6 gene cluster on chromosome 4 suggests that absence of the common haplotype is associated with increased risk for developing chronic active disease in patients who initially presented with Löfgren syndrome [40]. Another study examined the functional role of different TLR2 coreceptors and found that sarcoidosis BAL cells show differential responsiveness of these pathways, with increased production of TNF and IL6 in response to ligands for the TLR-2/1 heterodimer and reduced responses to TLR-2/6 ligands [39]. A role for TLR2 in sarcoidosis is further supported by animal models where experimental granulomatous inflammation is attenuated in the absence of functional TLR2 [37,39].…”
Section: Genetic and Immunologic Interactions In Sarcoidosis Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that these receptors detect PAMPs originating from intracellular pathogens (Lund et al 2003;Hemmi et al 2000) which is important in sarcoidosis where intracellular pathogens are important. However, evidence for a potential role of TLRs is suggested by evidence that BAL cells from sarcoidosis patients exhibit increased cytokine responses to the 19-kDa lipoprotein of Mycobacterium tuberculosis (LpqH), a TLR2/1 ligand, and decreased responses to the TLR-2/6 agonist fibroblast stimulating ligand-1 (FSL)-1 (Gabrilovich et al 2013).…”
Section: -Role Of Pattern Recognition Receptors In Sarcoidosismentioning
confidence: 99%